DESIGN OF A 10 TONS OVERHEAD CRANE WITH 21 METERS SPAN USING FINITE ELEMENT METHOD - Anton Heriawan; Muhamad Fitri (Universitas Mercu Buana, 2022)
A crane is a lifting equipment widely used to move cargo, construction sites, storage, and unload. The type of crane that is commonly used in industrial environments is the overhead crane. The overhead crane functions as a lifting device. Besides that, it also works as a load transfer tool even though the load being moved is limited to an environment that is not too large (indoor) at PT. A overhead crane is designed to overcome the problem of moving material in the mold storage area due to the area's expansion and the addition of 5-7 tons of mold material. Therefore, proper design is needed so the overhead crane can function properly. The design method uses the VDI 2221 or Finite Element with Solid works software. The results of the structure obtained are double box girder type girders with dimensions p = 21 m, t = 1224 mm, and l = 600 mm. The deflection results are 13.75 mm, and the runway uses steel profile I with dimensions 400 x 200 x 8 x 13 mm, with a deflection value at the runway stem of 5.6 mm. The type of wire rope used is type 6 x 37, with a diameter of 28 mm. The stress that occurs in the steel rope is 4306.1 Kg, less than the maximum allowable tensile stress of 8009.4 Kg. The single hook type with a hook diameter of 120 mm is made of material S45C. The tensile stress on the hook is 0.88 Kg, and the result is smaller than the allowable tensile stress of 12.72 Kg. The pulley diameter is 630 mm, the drum diameter is 604.9 mm, and the drum length is 279 mm.